Correlation of angle kappa with biometry and higher-order aberrations of cataract patients at Prof. Ngoerah Hospital Ophthalmology Clinic - Siska, Siska; Suryaningrum, I Gusti Ayu Ratna; Evani, Saphira (Faculty of Medicine, Universitas Trisakti, 2023)
Background Advancements in ophthalmic surgery now hinge on intricate interplays among ocular parameters. Angle kappa, measuring deviation between visual and pupillary axes, is crucial, especially in refractive procedures with multifocal intraocular lens implants. The research aimed to correlate angle kappa with biometry and higher-order aberrations (HOA) to enhance surgical outcomes among adult cataract patients at Prof. Ngoerah Hospital Ophthalmology Clinic, Denpasar, Bali. MethodsThis cross-sectional study included 29 male and female cataract patients aged 18-80 years, without prior treatment. All patients had a basic examination that included testing of visual acuity using Snellen chart, autorefractometer, measurement of ocular pressure using non-contact tonometry, and slit-lamp examination for cataract grading. Patients who met the inclusion criteria were then examined for biometry (axial length, spherical equivalent, white-to-white distance, anterior chamber depth) using Nidek AL Scan and for angle kappa and HOA using OPD scan III. ResultsData from 50 eyes of 29 subjects (15 females and 14 males) were analyzed. The mean age of the subjects was 60.6 ± 12.5 years. Age and spherical equivalent had positive correlation with angle kappa (r =0.104, r=0.213), but the correlation was not statistically significant. In this study, interestingly angle kappa was not significantly correlated with HOA, AXL, WTW, and ACD (r = -0.050, r = -0.192, r = -0.104, r = -0.195, p >0.05). ConclusionIn conclusion, angle kappa may increase with age and spherical equivalent. Further study with larger sample size is required.